Medieval Islamic economic thought: filling the ‘Great Gap’ in European economics. Edited by S. M. GHAZANFAR (London: RoutledgeCurzon, 2003), 299 pp. Price HB £55.00. ISBN 0–415–29778–8 - Haneef, Mohamed Aslam (Oxford University Press, 2004)
Books on the history of economic thought are a relatively rare find these days, more so in the nascent discipline of Islamic economics, which some would say has been ‘hijacked’ by works in the areas of banking and finance. While the editor rightly points out that this book is not about Islamic economics, it discusses a very important contribution to the development of contemporary Islamic economic thought, that is, the economic thought of selected ‘medieval Islamic scholastics’ who wrote within a five-hundred-year period from roughly 700 AD to 1200 AD, a period termed by Schumpeter as the ‘great gap’ in Western/European economic thought. Challenging Schumpeter’s great-gap thesis, Ghazanfar’s aim is to present the thought of the Arab-Islamic scholars of that period as the natural successors of post-Greek/pre-Enlightenment thought, including that of economics. To quote him, the aim of the book is ‘to demonstrate the considerable influence of Arab scholars on economic thought as it evolved from scholastic writings and to point out a serious omission in the history of economic science—indeed, in the history of ideas—of the profound contributions made by these scholars’ (p. 18).